Effectiveness of the Implementation of the Basic Food Assistance (Sembako) Program in Improving the Welfare of the Underprivileged Community - Nurul Nabila Afifah; W Windawati; Siti Khumayah (CV. Media Digital Publikasi Indonesia, 2025)
This study aims to analyze the effectiveness of the implementation of the Basic Food Assistance Program by the Cirebon Regency Social Service in improving the welfare of the underprivileged community. The focus of the study is directed at five indicators of effectiveness based on Campbell J.P.'s theory (1970), namely program success, target success, satisfaction with the program, input-output levels, and achievement of overall goals. This study uses a qualitative descriptive approach through research activities. Data collection techniques are carried out through observation, document studies, and interviews. The results of the study indicate that the implementation of the Basic Food Assistance Program still faces several problems, such as inaccurate recipient targets, inaccurate poverty data, low understanding of beneviciary, limited implementing resources, and minimal long-term impact evaluation. To improve the effectiveness of the program, improvement strategies are needed including data updates, strengthening the capacity of implementers, digitizing the system and increasing social literacy.